The Asian way and modern liberalism: A Hayekian perspective - KUKATHAS, Chandran (Institutional Knowledge at Singapore Management University, 1999)
F.A. Hayek was a European economist and socialphilosopher who first came to scholarly prominencefor his work on trade cycles and his disagreementswith John Maynard Keynes; and who earned widerintellectual notice (if not notoriety) for hispolemics warning of the threat to westerncivilisation posed by modern socialism. Hiseconomic writings in the 1930s aimed,more than anything, at exposing the flawsand contradictions in socialism as aneconomic system. His polemic, The Roadto Serfdom, published in 1944 with adedication to ‘The Socialists of All Parties’,was an attempt to turn around the thinkingof western policy-makers he thought tooeasily seduced by the claims of centraleconomic planning. And his treatise, TheConstitution of Liberty, published in 1960with a dedication to ‘The UnknownCivilisation Growing in America’, attempted to set out ina systematic way – and defend – the principles of classicalliberalism, which he understood as a political philosophywhich had evolved with the ‘progress’ of Europeancivilisation over the past several hundred years. Hayek didnot travel much in Asia, though he visited Japan and washappy to see his work translated and discussed there; nordid he write anything substantial about Asia. There is apassing reference to Confucius in Law, Legislation andLiberty, but little else that might suggest any significantacquaintance with Asian thinkers or Asian philosophy